Буковинські липовани: поява на території краю і значення етноніма в усній традиції - Воротняк, Іван Дмитрович (My University, 2022)
У статті автор аналізує зміст усних свідчень, наявних у середовищі буковинських липован про час і обставини переселення їхніх предків на територію краю, а також етимологію етноконфесіоніма «липовани». Як відзначають дослідники, серед сучасних старообрядців і досі побутують усні оповідання, в яких зафіксований процес розселення у володіннях Габсбурґів. Зазвичай носіями усної традиції виступають представники старшого покоління, які у свою чергу чули розповіді від своїх батьків. Вони і передають інформацію наступним поколінням. Практично всі липовани, незважаючи на свій вік, демонструють свою обізнаність із цього питання. Буковинські липовани називали себе так, не вбачаючи в цьому нічого осудного. Як пояснювали самі інформатори, це робилося для того, щоб про них не дізналися росіяни. Дослідники вважають таке пояснення логічним, зважаючи на пережиті гоніння після реформи патріарха Никона.
In this article, the author analyzes the content of oral evidence available among the Bukovynian Lipovans about the time and circumstances of the resettlement of their ancestors to the territory of the region, as well as the etymology of the ethno-confession name «Lipovans». As the researchers note, among modern Old Believers there are still oral stories that record the process of settling in the possessions of the Habsburgs. Usually, representatives of the older generation act as carriers of the oral tradition, who, in turn, heard stories from their parents. They pass on information to the next generation. Almost all Lipovans, despite their age, demonstrate their awareness in this matter. Note that their level of awareness depends on their personal interest in their own past and on the amount of accumulated facts. Usually such legends exist in the form of a tribal tradition. In the folk environment, several variants of legends about the appearance of the ethnonym «Lipovans» have developed. They are based on: a) characteristics of the terrain; b) the names of the original settlements; c) the names of the leaders. The most popular opinion is that the first settlers settled in linden forests, that is, the term «lipovan» comes from the name of the linden tree. Bukovynian Lipovans called themselves that, not seeing anything sane in it. As the informants themselves explained, this was done so that the Russians would not find out about them. Researchers consider this explanation logical, given the previous persecution after the reform of Patriarch Nikon. In everyday life, a certain distinction was formed in the use of terms, each of which occupied its own sphere: in everyday use and in publications on everyday topics – «Lipovans»; in publications that cover the life of the community – «Russian-Lipovanі»; in church life – «Old Believers». Such a division of spheres of application also determines the further coexistence of the ethnonym «Lipovans» and the accompanying designations of the Bukovynian Old Believers diaspora.
Keywords: Буковина, липовани, росіяни-старообрядці, етноконфесіонім, усна традиція; Bukovyna, Lipovans, Russian Old Believers, ethno-confessional name, oral tradition